EKSISTENSI KESENIAN KUDA LUMPING SISWO BUDOYO DI DUSUN SERASAU JAYA DESA PENITI KABUPATEN SEKADAU - Pratama, Rio; Noor, Agus Sastrawan; Firmansyah, Andang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis research aims to determine the existence art of kuda lumping Siswo Budoyo in Dusun Serasau Jaya Village Peniti District Sekadau. Mutual awereness in preserving art and culture is an important so that the objectives can be achieved in this art animating process. The research method used is qualitative with a descriptive form. The data is observation and results of interviews and documentation. While data inspection is done by data triangulation comparing the results of interviews with observation and documentation. Based on the results of research conducted by researchers it can be concluded that the existence art of  kuda lumping can survive until now done with various efforts such as increasing the quantity of training time, renewing structures management, clarify budget cash holdings, recruit children as members to continue regeneration and multiply the show?s schedule. Siswo Budoyo?s development of art is evidenced by the opening of the caretaker when collaborating on performences so that the kuda lumping art can be enjoyed by anyone. Keywords: Art, Existence, Kuda Lumping Siswo Budoyo